Formation of a healthy lifestyle culture among future teachers - V. Yu. Sokolova (Вестник Самарского университета: История, педагогика, филология)
In educational institutions, much attention is paid to educational, physical education and health work, focusing on optimizing and maintaining the health of students. And such an aspect of influence on the formation of health-preserving competence of children as the health and psychophysical state of the teacher himself is underestimated. However, insufficient understanding of the future teacher of the value of their own health, the lack of skills in applying health-preserving technologies on their own life experience leads to a low level of culture of their own health, which will have negative consequences during future professional activity. This article considers the issue of the need to create a special educational environment for students of pedagogical universities, which will promote both motivation for a healthy lifestyle and the formation of practical skills in health preservation. The work describes the experience of teachers of the Department of Physical Education and Health Protection of the Donetsk State Pedagogical University named after V. Shatalov in reorganizing the content of classes in order to understand the importance of a healthy lifestyle as an integral part of the general and professional culture of a teacher by future teachers.